Program Pembelajaran Metode Tilawati Masa Pandemi Covid-19 Di TPQ Al-Huda tegalrejo badas-Kediri - Imroatul Azizah; Fadhil Akbar (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
This research takes the theme of the learning program of tilawati method, where learning tilawati method is a learning activity that has the goal that a person is able to read and write alqur'an where the person can see, read, recite, and understand and also make letters from the writings contained in the holy qur'an. The provision of learning and practice experience in practicing it is based on the process experienced by each child before learning because they will know to what extent their ability to read or write the Qur'an. This research was carried out during the covid pandemic, because of our limitations in all community service, one of the activities this time was to hold a learning program at TPQ Al-Huda and researchers focused on learning tilawati methods. In an increasingly modern era, the hope of parents to their children is to have a better quality in the field of religion, especially reading the Qur'an. However, the lack of interest of students in learning the tilawati method, is felt right by teachers who in this day and age children are more busy with playing gadgets at home. So, in this case learning and understanding the science of the Qur'an is very necessary in accordance with the rules of tajwid science where the law of studying the science of tajwid, tartil and tahsin is mandatory 'ain The results of research on the learning program of tilawati method at TPQ Al-Huda is, the program is carried out in Ponpes Darul Fatihin which runs in accordance with what is expected although there are certainly a few obstacles as outlined. The changes that occur in the santri after the program proves that the program has been able to change the progress of students in terms of spirituality. Students are already able to read the Qur'an well in accordance with the rules of the tajwid laws that he has learned.